Raymie nightingale - DiCamillo, Kate (Candlewick Press, 2016)
Hoping that if she wins a local beauty pageant her father will come home, Raymie practices twirling a baton and performing good deeds as she is drawn into an unlikely friendship with a drama queen and a saboteur.